Progresses in synthetic technology development for the production of l-lactide. Issue 47 (17th November 2021) - Meng, Xiangkun; Yu, Lei; Cao, Yitao; Zhang, Xu; Zhang, Yiyang
Abstract : l -Lactide is an important intermediate for the industrial production of polylactic acid (PLA). This mini-review aims to summarize typical works on its related synthetic technology development in recent years. Abstract : l -Lactide is an intermediate for the industrial production of polylactic acid (PLA). The chemical and optical purities of lactide determine the quality of the prepared PLA. It is of great challenge to synthesize l -lactide efficiently with high chemical and optical purities under the conditions applicable for industrial production. With the national plastic reduction order issued, developing biodegradable materials such as PLA has gradually become a hot topic, and the production of upstream lactide is the key technique for the whole industrial chain. This mini-review aims to summarize typical works on the related synthetic technology development in recent years.